The convergence of the Euler's method - Sălăjan (Pomian), Raluca Anamaria (Rev. Anal. Numér. Théor. Approx., 2010)
In this article we study the Euler's iterative method. For this method we give a global theorem of convergence. In the last section of the paper we give a numerical example which illustrates the result exposed in this work.